2022
DOI: 10.1186/s12913-022-08737-1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Chinese version of the Normalization MeAsure Development(NoMAD)

Abstract: Background The Normalization MeAsure Development (NoMAD) is a brief quantitative tool based on the Normalization Process Theory (NPT), which can measure the implementation process of new technologies and complex interventions. The aim of our study was to translate and culturally adapt the NoMAD into Chinese, and to evaluate the psychometric properties of the Chinese version of NoMAD. Methods According to the NoMAD translation guideline, we undertoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…For the NoMAD, findings were similar to other studies in a variety of settings and languages: English nursing, sport and behavioral health care (Finch et al, 2018), Chinese nursing and injury health care ( Jiang et al, 2022 ), Brazilian Portuguese HIV/AIDS clinical monitoring ( Loch et al, 2020 ), Swedish post-discharge collaborative care planning ( Elf et al, 2018 ), German prevention, primary care, and mental health care settings (Freund et al, 2023), and Dutch specialized and primary mental health care (Vis et al, 2019). Although all studies found acceptable internal consistency and factor structures, most suggested changing or omitting specific items.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For the NoMAD, findings were similar to other studies in a variety of settings and languages: English nursing, sport and behavioral health care (Finch et al, 2018), Chinese nursing and injury health care ( Jiang et al, 2022 ), Brazilian Portuguese HIV/AIDS clinical monitoring ( Loch et al, 2020 ), Swedish post-discharge collaborative care planning ( Elf et al, 2018 ), German prevention, primary care, and mental health care settings (Freund et al, 2023), and Dutch specialized and primary mental health care (Vis et al, 2019). Although all studies found acceptable internal consistency and factor structures, most suggested changing or omitting specific items.…”
Section: Discussionsupporting
confidence: 86%
“…NoMAD underwent a thorough development process (Rapley et al, 2018) and its conceptual and internal validity have been studied and confirmed in various settings ( Elf et al, 2018 ; Vis et al, 2019; Finch et al, 2018; Jiang et al, 2022 ; Loch et al, 2020 ; Freund et al, 2023). Confirmatory factor analysis (CFA) showed the model to approximate the data acceptably.…”
Section: Methodsmentioning
confidence: 99%
“…The current version of the NoMAD compares also favourably with regard to internal consistency and construct correlation against other translations of the measure into Dutch (17), Swedish (18), Brazilian Portuguese (19), and Chinese (20). In the Dutch NoMAD validation study (17), the four-factor model showed the best t with the observed data.…”
Section: Comparison With Previous Literaturementioning
confidence: 74%
“…Since its development, the NoMAD has been translated from the English original and used in multiple languages across different cuntries, settings, and studies (17)(18)(19)(20). The current study aimed to review several German translations and pilot applications, to validate the instrument and to publish an o cial German-language version of the NoMAD questionnaire for research and practice purposes.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above scales used by us were all translated versions, and the process of translating them into Chinese was as follows [ [ 32 , 33 ]]: interpretation, cross-cultural adjustment, trial run, and psychometric examination. Phase 1 interpretation: the forward translation process is done by two bilinguals (native Chinese speakers), and the reverse translation is done by two native English speakers who have not seen the original materials and tools.…”
Section: Methodsmentioning
confidence: 99%